"Pappu Can't Dance Saala" : dis-locating bodies in Bollywood song and dance sequences. - Nurril Hirfana Mohamed Noor. (2013)
This research paper seeks to analyze disability and Bollywood song and dance sequences within the last decade. Song and dance sequences are fixed structures which value and presume a particular body type over others, thus simultaneously creating binaries of ability/disability and normal/abnormal. Where are 'disabled' bodies then located? How is difference projected in these sequences? My research paper will address these questions in the following films: Khamoshi - The Musical, Koi Mil Gaya, Koyla, Black, Taare Zameen Par, My Name is Khan and Barfi!.